On the profitability of collusion in location games; Zur Profitabilität von Kollusion in Standortspielen - Steffen Huck; Vicki Knoblauch; Wieland Müller (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2002)
In this note we take a first step towards the analysis of collusion in markets with spatial competition, focusing on the case of pure location choices. We find that collusion can only be profitable if a coalition contains more than half of all players. This result holds for location games played in k-dimensional Euclidean space as long as consumers are distributed via atomless density functions. For competition on the unit interval, unit circle, and unit square we also derive sufficient conditions for collusion to be profitable. – – Wir untersuchen Kollusion in Märkten, in denen die einzige strategische Variable der Akteure ihre Ortswahl ist. Für Spiele in k-dimensionalen Euklidischen Räumen mit massepunktfreien Verteilungen zeigen wir, dass Kollusion nur profitabel sein kann, wenn wenigstens die Hälfte aller Akteure kolludieren. Für Wettbewerb auf dem Einheitsintervall, dem Einheitskreis und dem Einheitsquadrat etablieren wir hinreichende Bedingungen für die Profitabilität von Kollusion.
Keywords: 330